Upaya Memperkuat Pemahaman Sejarah Nusantara dan Malaysia melalui Knowledge Sharing Perjalanan Parameswara dari Swarnadwipa ke Malaka - Wedhowerti, Wedhowerti (Universitas Nusantara PGRI Kediri, 2025)
Collective memory between Indonesia and Malaysia needs to be refreshed in order to resolve misunderstanding that often occurs among the citizens of the two countries. A knowledge in the framework of community service is conducted to refresh the collective memory and improve historical knowledge. This is done by tracing back the historical journey of Parameswara from Swarnadwipa (Sumatra) to Malacca. The knowledge sharing is conducted in St. Francis’s Institution Malacca, Malaysia. There are around one hundred participants of different age and diverse ts participatingand diverse background participating in it. The results of this knowledge sharing is evident from the exceeding number of participant, question, and critical argument. Moreover, the discussion went on outside the knowledge sharing session. It is concluded that this knowledge sharing is successful in refresing the collective memory of the two nations’ history.